Multi-layer elemental 2D materials: antimonene, germanene and stanene grown directly on molybdenum disulfides. (17th September 2019) - Chen, Kuan-Chao; Lee, Lun-Ming; Chen, Hsuan-An; Sun, Hsu; Wu, Cheng-Lun; Chen, Hsin-An; Lin, Kuan-Bo; Tseng, Yen-Chun; Kaun, Chao-Cheng; Pao, Chun-Wei; Lin, Shih-Yen
Abstract: Similar material characteristics are observed for the elemental 2D material of group-V antimonene prepared by both molecular beam epitaxy and thermal evaporation on MoS2 surfaces. Group-IV germanene and stanene can also be prepared by using the same thermal evaporation technique. With the well stacked hetero-structures, lattice mismatch does not play an important role for van der Waals epitaxy between 2D materials. The observations of the elemental 2D materials instead of their conventional semiconductor structures on MoS2 surface demonstrate the preferential 2D structure formation on 2D material surfaces. Compared with the higher growth temperature of germanene, room-temperature growth is observed for stanene. The contact resistance reduction and the integration with the standard metal lift-off procedure on MoS2 surfaces has made stanene a promising candidate as the contact metal for 2D devices.